TOURISM DEVELOPMENT STRATEGY IN DAIRI REGENCY - Wiro Oktavius Ginting; Siti Hazzah Nur (DIA: Jurnal Administrasi Publik, 2022)
Tourism is a community need and the government's mainstay to earn non-oil and gas foreign exchange. Dairi is one of the regency that has huge tourism potential, but it has not been managed properly and has an impact on socio-economic conditions. The purpose of this study is to find out how the strategy that has been carried out by the Department of Tourism and Culture of Dairi Regency to develop tourism and to find out what strategies can be used to develop tourism. This research process begins by identifying and analyzing strategic values, internal and external environment, as well as supporting and inhibiting factors. The next process is determining strategic issues using SWOT analysis techniques and formulating tourism development strategies. The method is a descriptive research method with a qualitative approach. The steps used in data collection include: interviews, observation, documentation, and literature study. The strategies used in developing tourism include: SO strategy (Strength Opportunity), ST strategy (Strength Threat), WO strategy (Weakness Opportunity), and WT strategy (Weakness Threat). The results of the research on the SO strategy showed that Dairi Regency has good potential in the tourism sector due to its geographical location and a large number of tourism destinations. For ST strategy, the Department of Tourism and Culture in Dairi Regency always coordinates with relevant agencies in the maintenance and development of existing and new tourist destinations. The WO strategy found that there was a lack of financial support from the local government and inadequate human resources. The WT strategy found a lack of improvement in service quality, and uneven infrastructure development.